Implementation of Financing Compass for Welfare Partner Operational System Grameen Bank in Banyumas Regency - Apik Anitasari Intan Saputri (Ijtimā`iyya: Journal of Muslim Society Research, 2018)
Indonesia has a variety of microfinance service providers such as Commercial Banks, Rural Banks, Non-Bank Financial Institutions (LKBB), Micro Finance Institutions (MFIs), Savings and Loans Cooperatives (KSP) and other semiformal and informal institutions operating at the local community level. One Non-Bank Financial Institution operating in Indonesia is an institution with a group finance system - commonly referred to as Grameen bank. Its business objectives are to tackle poverty or other problems such as education, health, access to technology, and environmental issues that may threaten people and society. The research method used is field research with a sociological juridical approach. With the establishment of a poverty alleviation program involving many women, Grameen banks became one of the integrated institutions in public health programs by establishing sanitation and water programs as a health support product of its partners. This product is called KOMPAK and aims to develop financing products for the development of water quality and sanitation improvement among low-income people. Women Grameen bank actors are not only a target in the development of the business world, they also provide education on improving the quality of life and raise awareness of the importance of water hygiene and sanitation health. The company offers loans to economically active but low-income women especially those living in urban and rural areas.